2020
DOI: 10.1021/acs.biochem.9b00971
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Structures of the Influenza M2 Proton Channel Drug-Resistant V27A Mutant Bound to a Spiro-Adamantyl Amine Inhibitor Reveal the Mechanism of Adamantane Resistance

Abstract: The V27A mutation confers adamantane resistance to the influenza A matrix 2 (M2) proton channel and is becoming more prevalent in circulating populations of influenza A virus. We have used X-ray crystallography to solve structures of a spiro-adamantyl amine inhibitor bound to M2(22-46) V27A and also to M2(21-61) V27A in the Inward closed conformation. The spiroadamantyl amine binding site is nearly identical for the two crystal structures. Compared to the M2 "wild type" (WT) with valine at position 27, we obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 90 publications
6
56
0
Order By: Relevance
“…-S31N (19-49) in complex with (4) (PDB: 2LY0; ). (C) X-ray crystal structure of M2-V27A (22-46) in complex with spiro-adamantyl amine (9) (PDB: 6NV1; Thomaston et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-S31N (19-49) in complex with (4) (PDB: 2LY0; ). (C) X-ray crystal structure of M2-V27A (22-46) in complex with spiro-adamantyl amine (9) (PDB: 6NV1; Thomaston et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Ser31Asn is the prevalent mutation in more than 95% of adamantane-resistant strains (Dong et al, 2015;Nelson et al, 2009), although a recent study reported a potential rise in the frequency of virus strains containing the Val27Ala and Ser31Asn double mutations (Durrant et al, 2014). A recent crystallography study reported that elimination of hydrophobic contacts that are essential for adamantane drug binding is the underlying cause behind adamantane resistance to Val27Ala mutant (Thomaston et al, 2020). In contrast to the Val27Ala single mutation that results in complete resistance to amantadine, M2 sequences containing Ser31Asn can still be inhibited by amantadine in vitro, albeit with approximately 200-fold higher concentrations in TEVC experiments and plaque reduction assays (PRAs) and substantially higher than what is therapeutically-achievable (Wang et al, 2013a).…”
Section: The Rise Of Drug-resistant M2mentioning
confidence: 99%
“…Upon drug-resistance V27A mutation, this interaction is lost. Recentlydeveloped spiro-amantadyl amine effectively binds to A27 of the pore (Figure 2B) [136]. Recently, new amantadine derivatives effective against double mutants M2-S31N/L26I and M2-S31N/V27A viral strains have been developed by Musharrafieh et al [91].…”
Section: M2 Ion Channel Blockers (Amantadine/rimantadine)mentioning
confidence: 99%
“…3 Several groups published high resolution structures and data from mutation experiments showing that M2 protein channel is blocked by 1 and 2 via a M2 pore-binding mechanism. [4][5][6][7][8][9] Additionally, amantadine variants, especially those with hydrophobic adducts, can act as lysosomotropic drugs, 10 which accumulate in intracellular vesicles through membrane permeation by the electroneutral form and increase intravesicular pH, causing endosome and/or trans-Golgi network neutralization and inhibition of viral reproduction. 11 Noteworthy, SARS-CoV-2 is inhibited by chloroquine, probably because it acts as a lysosomotropic drug.…”
Section: Introductionmentioning
confidence: 99%